2017
DOI: 10.1038/s41598-017-06659-1
|View full text |Cite
|
Sign up to set email alerts
|

Multidimensional integrative analysis uncovers driver candidates and biomarkers in penile carcinoma

Abstract: Molecular data generation and their combination in penile carcinomas (PeCa), a significant public health problem in poor and underdeveloped countries, remain virtually unexplored. An integrativemethodology combin ing genome-wide copy number alteration, DNA methylation, miRNA and mRNA expression analysis was performed in a set of 20 usual PeCa. The well-ranked 16 driver candidates harboring genomic alterations and regulated by a set of miRNAs, including hsa-miR-31, hsa-miR-34a and hsa-miR-130b, were significant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
39
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(42 citation statements)
references
References 55 publications
1
39
0
2
Order By: Relevance
“…Androgen receptor has been described as a major oncogenic driver in prostate cancer [9]. In penile tumors, the AR gene was one of the top 10 putative drivers involved in genomic loss and regulated by oncomiRs, which was a plausible explanation for the mRNA lower expression levels [28]. In parallel, we showed that AR is at least 30 folds down-expressed in PeCa compared to normal tissues giving additional support for the involvement of this gene in penile carcinogenesis [19].…”
Section: Discussionsupporting
confidence: 67%
See 3 more Smart Citations
“…Androgen receptor has been described as a major oncogenic driver in prostate cancer [9]. In penile tumors, the AR gene was one of the top 10 putative drivers involved in genomic loss and regulated by oncomiRs, which was a plausible explanation for the mRNA lower expression levels [28]. In parallel, we showed that AR is at least 30 folds down-expressed in PeCa compared to normal tissues giving additional support for the involvement of this gene in penile carcinogenesis [19].…”
Section: Discussionsupporting
confidence: 67%
“…Molecular alterations in PeCa have been described only recently by our group and others [19,[21][22][23][24][25][26][27][28][29][30]. Interestingly, contrary to the findings described in breast and prostate cancers, AR mRNA is down-expressed in PeCa [19].…”
Section: Introductionmentioning
confidence: 63%
See 2 more Smart Citations
“…Furthermore, TGFB3 and TGFBR2 were found within the top pathways involving miRNA-targeted genes disrupted in penile cancer [291]. TGFBR2 was also predicted as one of the 47 candidate driver genes targeted by multiple miRNAs, the expressions of which were altered in penile cancer samples compared with normal penile tissue [292]. None of these studies, however, included functional analysis to validate the miRNA-mediated regulation of TGF-β pathway genes, nor the TGF-β-mediated regulation of miRNAs.…”
Section: Penile Cancermentioning
confidence: 93%